Damage Tolerance of Carbon Fiber Woven Composite Doped with MWCNTs under Low-velocity Impact. (2017) - Rawat, Prashant; Singh, Kalyan Kumar
Abstract: Fiber reinforced polymer (FRP) composites have versatile application as advanced structural material in many industries. Light weight, high aspect ratio with unique mechanical, electrical, thermal properties make it future of advanced material applications. This study addresses the enhancement in damage tolerance of carbon fiber laminate using multiwall carbon nanotubes (MWCNTs) as well as optimum value for maximum augmentation has been proposed. MWCNTs reinforced (neat, 0.25%, 0.50%, 0.75% and 1% of resin weight) carbon fiber laminates were fabricated. The carbon fiber woven composite laminate with eight layers and symmetrical design were fabricated using hand lay-up technique assisted by vacuum bagging method at 0.9 mm of Hg pressure. Results confirmed that reinforcing MWCNT enhancement in damage tolerance is possible and 0.25 wt. % is optimum doping value to achieve maximum damage tolerance.